Exploring the Mahuang Fuzi Xixin Decoction’s mechanism for treating Alzheimer’s disease using molecular docking and network pharmacology - Chen, Che; Shao, Qianfeng; Zhou, Sheng (Frontiers in Aging Neuroscience, 2025)
ObjectiveExplore the potential mechanism of Mahuang Fuzi Xixin Decoction (MFXD) in the treatment of Alzheimer’s disease (AD) using network pharmacology, molecular docking approaches, and test its efficacy by in vitro experiments.MethodsActive components of MFXD were screened from TCMSP, BATMAN-TCM, and TCMID, with corresponding targets obtained from SwissTargetPrediction and TCMSP. AD-related differential genes were retrieved from GEO. Intersection targets were identified via Venn diagrams, followed by GO/KEGG enrichment analyses, PPI network construction, and molecular docking. In vitro validation experiments were carried out using PC12 cells induced by Aβ25–35 to simulate the pathological state of AD. For the detection of cell viability, the CCK-8 assay was employed to evaluate the protective effect of MFXD and its active components on damaged PC12 cells. Western blot analysis was used to determine the protein expression levels of key molecules involved in AD-related signaling pathways, including phosphorylated p-NF-κB p65, NF-κB p65, p-GSK-3β, GSK-3β, MMP-9, p-Tau, and Tau. Additionally, the ELISA was utilized to measure the secretion level of TNF-α in the supernatant of Aβ25–35-induced PC12 cells, so as to assess the anti-inflammatory effect of MFXD.ResultsThirty-seven active components and 230 targets of MFXD were identified, along with 4913 AD-related differentially expressed genes from GEO dataset GSE122063, yielding 47 intersection targets. GO annotation enriched these targets in processes like reactive oxygen species metabolism, components like extracellular matrix, and functions like neurotransmitter binding; several pathways were enriched in the KEGG analysis, such as TNF signaling pathway, calcium signaling pathway, and NF-κB signaling pathway. The intersection target PPI network identified MMP9, EGFR, FOS as core targets. Molecular docking results indicated that quercetin binds to the three core targets (MMP9, EGFR, FOS), while luteolin binds preferentially to EGFR and MMP9. In vitro, Aβ25–35-induced PC12 cells treated with quercetin/luteolin had concentration-dependent viability increases (all P < 0.001); 15% MFXD-containing serum restored viability to ≥ 95% (P < 0.001 vs. AD model, comparable to DHCL). Western blot showed AD model had elevated p-NF-κB p65/NF-κB p65, MMP9/β-actin, p-Tau/Tau and reduced p-GSK-3β/GSK-3β (all P < 0.05); MFXD reversed these (all P < 0.05), while DHCL only inhibited p-NF-κB p65/NF-κB p65. ELISA showed MFXD and DHCL both reduced AD model’s TNF-α (all P < 0.001).ConclusionMFXD potentially exerts anti-AD effects through a multi-component, multi-target, multi-pathway approach. Its key active components (quercetin, luteolin) may act by modulating the core target MMP9. Also, MFXD can simultaneously regulate several pathways, such as the TNF signaling pathway, Calcium signaling pathway, and NF-κB signaling pathway, and target Tau protein-related pathology by restoring the phosphorylation level of GSK-3β to suppress abnormal hyperphosphorylation of Tau, and thereby alleviating pathological damage in AD.